Digitalizing Assessment : An E-Report Application for Supporting Accountability in Merdeka Curriculum-Based Learning - Putri, Daning; Ismanto, Bambang; Satyawati, Sophia Tri (Jurnal Paedagogy, 2025)
This study aims to analyze the utilization of the current E-Report system in managing student assessments, identify the challenges encountered in the assessment process, and explore the development of an enhanced E-Report application to improve assessment accountability. The research adopts a Research and Development (R&D) approach based on the Borg and Gall model, implemented up to the fifth stage, and employs a mixed-methods design integrating both quantitative and qualitative data to obtain a comprehensive understanding of system use and development. The study was conducted at SMP Negeri 1 Bandungan, Semarang Regency, Central Java Province, involving teachers, system operators, and the vice principal for curriculum affairs as research participants. Data were collected through interviews, observations, document analysis, and questionnaires. Research instruments included interview guides, observation sheets, assessment documents, and validation questionnaires. Qualitative data validity was ensured through technique and source triangulation, while quantitative data validity was established through expert judgment. The findings indicate that the manual process of inputting assessment descriptions requires simplification to enhance efficiency and effectiveness. The Microsoft Excel–based E-Report application developed in this study provides flexible access and facilitates more efficient data management. Validation results showed scores of 88% and 94% from two management experts and 94% from an ICT expert. User testing results demonstrated ratings of 98.06% for display quality, 92.50% for technical quality, and 88.33% for accessibility. Overall, the application is categorized as “very good” and proven effective in enhancing assessment accountability.